A Proposed Reading Program for Secondary School Students - Dr. Caren Rimando Bansolay (International Journal of Engineering and Management Research, 2018)
This proposed program presents a background of reading competencies, application of consistent methodological standards and technology-assisted programs. Several researches have quoted the arising complication in the education of high school students, especially in the learning of reading as part of the English subject because of the advancement of technology. Clearly, well-educated programs established a decade ago are no longer effective nowadays. Moreover, it focuses specifically on teaching reading to fourth year high school students with the assistance of multimedia. Some researches on the use of multimedia digital technologies to enhance reading instruction are in its infancy. This reflects the fact that the technological capabilities that appear to have the most potential in aiding children learn how to read, such as computer speech recognition, have only recently become sufficiently affordable and available for widespread use. In addition, this reading program is intended to provide background information that will encourage reading specialists, education technology specialists, classroom teachers, and special education teachers to work together to understand, evaluate and implement effective uses of technology in teaching reading to students. It brings together the research-based guidelines for teaching students to read with information about the potential uses of multimedia digital technology to enhance reading instruction.